Antimicrobial and antitumor activity of S-methyl dithiocarbazate Schiff base zinc(II) complexes - Ramilo-Gomes, Filipa; Addis, Yemataw; Tekamo, Israel; Cavaco, Isabel; Campos, Débora L. [UNESP]; Pavan, Fernando R. [UNESP]; Gomes, Clara S.B.; Brito, Vanessa; Santos, Adriana O.; Domingues, Fernanda; Luís, Ângelo; Marques, M. Matilde; et al. (Elsevier, 2021)
Schiff bases (SB) obtained from S-methyl dithiocarbazate and aromatic aldehydes: salicylaldehyde (H2L1), o-vanillin (H2L2), pyridoxal (H2L3) and 2,6-diformyl-4-methylphenol (H3L4), and their corresponding Zn(II)-complexes (1–4), are synthesized. All compounds are characterized by elemental analyses, infrared, UV–Vis, nuclear magnetic resonance spectroscopy and mass spectrometry. The structures of H2L2 and [Zn2(L1)2(H2O)(DMF)] (1a) (DMF = dimethylformamide) are solved by single crystal X-ray diffraction. The SB coordinates the metal center through the Ophenolate, Nimine and Sthiolate atoms. The radical scavenging activity is tested using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay, with all ligand precursors showing IC50 values ~40 μM. Cytotoxicity studies with several tumor cell lines (PC-3, MCF-7 and Caco-2) as well as a non-tumoral cell line (NHDF) are reported. Interestingly, 1 has relevant and selective antiproliferative effect against Caco-2 cells (IC50 = 9.1 μM). Their antimicrobial activity is evaluated in five bacterial strains (Klebsiella pneumoniae, Acinetobacter baumannii, Listeria monocytogenes, Pseudomonas aeruginosa and Staphylococcus aureus) and two yeast strains (Candida albicans and Candida tropicalis) with some compounds showing bacteriostatic and fungicidal activity. The minimal inhibitory concentration (MIC90) of HnL against Mycobacterium tuberculosis is also reported, with H2L2 and H3L4 showing very high activity (MIC90 < 0.6 μg/mL). The ability of the compounds to bind bovine serum albumin (BSA) and DNA is evaluated for H3L4 and [Zn2(L4)(CH3COO)] (4), both showing high binding constants to BSA (ca. 106 M−1) and ability to bind DNA. Overall, the reported compounds show relevant antitumor and antimicrobial properties, our data indicating they may be promising compounds in several fields of medicinal chemistry.
Keywords: Anticancer; Antimicrobial; DNA; S-methyl dithiocarbazate; Schiff bases; Zn(II) complexes